“Can Modelling Be Taught and Learnt?” – A Commentary - Borba, Marcelo C. [UNESP] (Springer Nature, 2011)
The questions, whether mathematical modelling can be learnt and what we know from empirical research, are highly relevant not only for the current research on modelling, but they are as well essential for curricular changes introducing modelling into schools. Werner Blum tackles these questions in his paper from several perspectives and shows important research regarding the possibilities of students and teachers learning and teaching modelling, respectively. Blum dedicates his research to cognitive analysis of students who are involved in developing modelling tasks with the help of teachers.
Keywords: Goal Orientation; Modelling Activity; Modelling Task; Teacher Learning; Teaching Modelling